Symptoms Depression Among Elderly Women with Cervical Cancer: A Psychological Profile Study - Vivi Sovianti; Nella ValenIka Puspita; Rusmiyati Rusmiyati (Indonesian Journal of Global Health Research, 2026)
Depression is a psychological problem that often occurs in cancer patients due to an imbalance of neurotransmitters such as serotonin, norepinephrine, and dopamine that affect mood, anxiety, and cognition. This study aims to determine the relationship between elderly characteristics and depressive symptoms in cervical cancer patients. Method: The study used a descriptive design with a cross-sectional approach on 76 elderly respondents from a total population of 102 people, who were selected using purposive sampling based on inclusion and exclusion criteria. The research instrument used the Geriatric Depression Scale (GDS) with 15 questions, and the data were analyzed descriptively using a crosstab test. The results showed that most respondents were in the pre-elderly age (73.7%), unemployed (68.4%), married (82.9%), had suffered from cancer for more than six months (65.8%), and were in stage III (47.4%). Based on GDS measurements, the majority of respondents experienced mild depression (51.3%). The analysis showed a tendency that age, occupation, marital status, duration of illness, and cancer stage were related to the level of depression. Most elderly women with cervical cancer experience mild depression, so early screening and psychological intervention with a bio-psycho-social approach are needed to improve quality of life and treatment success.